Tracking Love in the Wild: from San Diego to Athens, Greece and Beyond - Halkias, Alexandra (Imaginations, 2019)
The animal is a border guard; produced socially and historically in ways that work for an array of (neo)colonizing state-building projects. Here I attempt to destabilize 'the animal' while tracking pathways for a form of relationality which reveals it as a political instrument that is powerful and deadly. Of interest is a state of being wherein relationality between human and non-human animals becomes a force that is transformational. A state of being wherein the human is the feline; wherein humor is not exclusively human. A new politics of vision is at stake. This paper-collage seeks to open up this ground.